Quality of Iranian EFL Learners’ Argumentative Essays: Cohesive Devices in Focus - Dastjerdi, Hossein Vahid; Samian, Samira Hayati (Mediterranean Journal of Social Sciences, 2011)
The ability to compose a piece of argumentative text is important for EFL and ESL learners. Despite its importance, thereis a gap in the literature about how Iranian students write essays in this genre that this study intends to fill. Building upon Halliday andHasan's (1976) cohesion theory, this study intended to investigate Iranian graduate non-English majors' use of cohesive devices inargumentative essays, and also the relationship between the number of cohesive devices and writing quality. An analysis of fortyargumentative essays written by forty Iranian graduate non-English majors showed that the students were familiar with various cohesivedevices and used them in their writings. Among the cohesive devices used lexical devices had the largest percentage of the total number ofcohesive devices, followed by reference devices and conjunction devices. Furthermore, it was found that there was no significant relationshipbetween the number of cohesive devices used and quality of writing. The findings of the study have some important implications for EFLwriting teachers and learners.